2014
DOI: 10.1155/2014/246096
|View full text |Cite
|
Sign up to set email alerts
|

Advance in ERG Analysis: From Peak Time and Amplitude to Frequency, Power, and Energy

Abstract: Purpose. To compare time domain (TD: peak time and amplitude) analysis of the human photopic electroretinogram (ERG) with measures obtained in the frequency domain (Fourier analysis: FA) and in the time-frequency domain (continuous (CWT) and discrete (DWT) wavelet transforms). Methods. Normal ERGs (n = 40) were analyzed using traditional peak time and amplitude measurements of the a- and b-waves in the TD and descriptors extracted from FA, CWT, and DWT. Selected descriptors were also compared in their ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
6

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 35 publications
1
38
0
6
Order By: Relevance
“…The DWT generates scalograms (Figure 1(a)) which display the energy ( z -axis) of the signal (maximal values are shown in red; lowest values in blue) as a function of time ( x -axis) and frequency ( y -axis). As previously demonstrated by us and others [10, 13, 1518], this time-frequency approach allows for the identification of energy descriptors, each defined with their respective time and frequency coordinates. The DWT yields measurements of the photopic b-wave (found in the 20 and 40 Hz bands) and OPs (found in the 80 and 160 Hz bands) through the quantification of their respective associated wavelet coefficients [10, 16, 17].…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…The DWT generates scalograms (Figure 1(a)) which display the energy ( z -axis) of the signal (maximal values are shown in red; lowest values in blue) as a function of time ( x -axis) and frequency ( y -axis). As previously demonstrated by us and others [10, 13, 1518], this time-frequency approach allows for the identification of energy descriptors, each defined with their respective time and frequency coordinates. The DWT yields measurements of the photopic b-wave (found in the 20 and 40 Hz bands) and OPs (found in the 80 and 160 Hz bands) through the quantification of their respective associated wavelet coefficients [10, 16, 17].…”
Section: Methodsmentioning
confidence: 91%
“…As previously demonstrated by us and others [10, 13, 1518], this time-frequency approach allows for the identification of energy descriptors, each defined with their respective time and frequency coordinates. The DWT yields measurements of the photopic b-wave (found in the 20 and 40 Hz bands) and OPs (found in the 80 and 160 Hz bands) through the quantification of their respective associated wavelet coefficients [10, 16, 17]. As exemplified in the scalogram of Figure 1(a), two DWT descriptors were used to quantify the 20 Hz and 40 Hz b-wave energy (identified as 20b and 40b) and another two were used to quantify the 80 Hz and 160 Hz OPs energy (identified as 80ops and 160ops), each computed by summating values outlined by the white boxes, respectively.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, the discrete wavelet transform (DWT) is a wavelet-based approach to analyze non-stationary signals that has recently been used to extract the a- and b-wave components of the single flash ERG [15,16]. The DWT permits localizing the energy content of the ERG in both time and frequency, and it has been suggested that this approach may be able to identify subtle diagnostic features of the ERG that are less apparent in time domain measures [16].…”
Section: Introductionmentioning
confidence: 99%